Credit evaluation model for working capital using Python language applied to public banking: Case study in shrimp project - Cordero, Bernardo (2021)
Macroeconomic theories and microeconomic fundamentals are studied to evaluate both the systematic risk and the specific risk of investment projects respectively. Consisting of two parts, the evaluation model contemplates the use of multiple regression in the Python programming language to analyze the variableprice dependent on other variables in the shrimp and prawn wholesale sector. Next, in a graphical way, the economic and financial performance of the shrimp company was quantitatively contrasted for its projection of the free cash flow (FCF) to analyze its viability of leverage with Banecuador BP, Corporación Financiera Nacional and Banco del Pacífico. Complementary to the net present value (NPV) and Internal Rate of Return (IRR) project decision indicators, the generation of value was calculated using the return on invested capital (ROIC) and the weighted average cost of capital (WACC) rate. ).